PERBEDAAN GRIT PADA MAHASISWA PERANTAU DAN BUKAN PERANTAU DI UNIVERSITAS “X” - Shanty Sudarji; Fifi Juniarti (Psyche: Jurnal Psikologi, 2020)
Family support, especially parents, can help students adapt to their educational transition from high school to college or university. For overseas students, of course the limited presence of parents will be a challenge as well as a separate opportunity to develop themselves. In addition to supporting factors the encouragement of intrinsic motivation from students' personalities also determines in an effort to get good academic achievement. One of the personality traits that helps a person to be able to maintain his intrinsic motivation is Grit, one of the concepts put forward by Angela Lee Ducksworth. Grit has two aspects, namely perseverance of effort and consistency of interest. The research instrument for measuring Grit will use a measuring instrument developed by Angela Lee Duckworth (2009). Measuring instruments in the form of a self-report questionnaire, validity r = 0,300-0,654 and reliability r = 0,888. Respondents from this study were 344 university X students with respondents' ages varying from 17 to 24 years. The mean score of the Grit variable in the Overseas group of students was 37.05 while the mean score in the non-Overseas group of students was 35.17. Overseas student groups showed higher Grit scores than non-overseas student groups. Individuals who have higher grits will be more diligent and diligent, are not easily discouraged by setbacks or failures, are more focused on projects or goals, and are more likely to complete tasks. Keywords: grit, non-overseas students, overseas students